Malicious innocence - Swihart, Sam, author; Osborne, Erika, advisor; Lehene, Marius, committee member; Moore, Emily, committee member; Cooperman, Matthew, committee member (Colorado State University. Libraries, 2016)
My work represents an exploration of warfare through the lens of children both in and out of the combat zone. Because warfare is such a multifaceted enigma, many of its aspects become overlooked in favor of grandiose narratives that speak towards its glorification or abhorrence. In the past, art was used to ennoble warfare as a kind of sport for the aristocracy, while legitimizing conflict through the actions of the ruler and state. However, beginning in the nineteenth century, there was a shift in propaganda that focused more intensely on the role of the individual soldier. By the twentieth century the focus had shifted largely away from the valor of individuals, instead focusing ever more on the abject qualities of modern warfare. These narratives all share a common theme that is primarily focused on the actions of individual soldiers or units, their heroism, and the horrors they endured. Yet children often play an ancillary role in many of these narratives, either providing a source for pity, or showing desperation while emphasizing the loathsomeness of an enemy. For this reason, I have chose to tackle the subject from a different angle – that of the child’s involvement both in play as well as combat. By exploring the often overlooked role of children both in actual conflict as well as the social roles of children on the home front in times of war I hope to examine not only the effects of battle on the child, but also the cultural conditioning of children to further perpetuate the cycle of violence through the reinforcement of societal norms. To achieve this I have been playing off the duality of chaos by juxtaposing imagery of children at play with imagery of war and its consequences. Throughout this exploration my work has made several dramatic aesthetic shifts in an effort to communicate this sense of chaos – psychologically as well as physically. By combining traditional, indirect painting methods with contemporary photorealism, I hope to create visual tension between areas that are fully rendered as well as areas that are under developed and deliberately obscured. I have also begun the use of photo collage in the creation of my paintings in an effort to further destabilize the visual field and to bring an additional air of uncertainty to the narrative. Furthermore my palette has shifted away from a traditional, limited palette to incorporate a variety of colors. These help to emphasize the more unsettling aspects of the subject. By incorporating these elements of painting into the work I hope to represent a sense of disorientation that echoes the abstruseness of war itself.
Keywords: painting; children; warfare